2010
DOI: 10.1111/j.1600-0854.2010.01036.x
|View full text |Cite
|
Sign up to set email alerts
|

TIP47 is Required for the Production of Infectious HIV-1 Particles from Primary Macrophages

Abstract: Macrophages are among the major targets of HIV-1 infection and play a key role in viral pathogenesis.Identification of the cellular cofactors involved in the production of infectious HIV-1 from macrophages is thus crucial. Here, we investigated the role of the cellular cofactor TIP47 in HIV-1 morphogenesis in primary macrophages. Using siRNA approach, we show that TIP47 is essential for HIV-1 infectivity and propagation. TIP47 silencing disrupts Gag and Env colocalization in macrophages. Moreover, mutations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 46 publications
(75 reference statements)
1
19
0
Order By: Relevance
“…It has been shown that point mutations in either MA or the CT of Env, that disrupt Env incorporation by altering their direct or indirect interactions at the site of assembly, did not decrease the intracellular levels of Env as was observed in our Ubc9 knockdown cells [97,110–113]. Furthermore, knockdown of Tip47, a host protein reported to be involved in Env incorporation and retrograde transport to the TGN from the PM, did not result in decreased intracellular Env levels [4,26,27]. In addition we did not observe changes in intracellular levels of host cell surface proteins E-cadherin (Figure 3) and TfR (data not shown), both of which also undergo AP-2/clathrin dependent endocytosis [114116].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…It has been shown that point mutations in either MA or the CT of Env, that disrupt Env incorporation by altering their direct or indirect interactions at the site of assembly, did not decrease the intracellular levels of Env as was observed in our Ubc9 knockdown cells [97,110–113]. Furthermore, knockdown of Tip47, a host protein reported to be involved in Env incorporation and retrograde transport to the TGN from the PM, did not result in decreased intracellular Env levels [4,26,27]. In addition we did not observe changes in intracellular levels of host cell surface proteins E-cadherin (Figure 3) and TfR (data not shown), both of which also undergo AP-2/clathrin dependent endocytosis [114116].…”
Section: Discussionmentioning
confidence: 70%
“…Env and Gag have been hypothesized to first interact and influence each other at an intracellular site, at or near the TGN or recycling endosomes [19,26,27,43]. It is possible that the interruption of normal Gag-Ubc9 interactions in the Ubc9–depleted cells may also affect Gag-Env interactions to lead to a disruption of their co-trafficking to the site of assembly.…”
Section: Discussionmentioning
confidence: 99%
“…This study also provides evidence that mutations at the Y 802 W 803 diaromatic motif or at the LL 800 dileucine motifs involved in TIP47 and prohibitin binding respectively [54, 121] affect cell-free virus infection but not cell-to-cell propagation [120]. In contrast to this report, we found that both cell-free and cell-to-cell fusion of viruses with subtype C gp41CT were affected, although to different degrees for different viral strains (e.g.…”
Section: Discussionmentioning
confidence: 90%
“…Endocytosed Env can either proceed to be degraded by lysosomes or be sorted back to the Golgi by interacting with retromer components Vps26 and Vps35 via is1 and is2 [65] or with a number of other proteins which regulate its traffic through the TGN and back to the PM. These include TIP47 through the Y 802 W 803 diaromatic motif [5054], AP-1 and AP-3 through the Y 712 SPL and the C-terminal dileucine LL 856 motifs [61, 63, 64] and Rab11a/FIP1C and Rab14 through the YW 795 diaromatic motif [55, 66]. AP-2-mediated internalization of Env is reversed by the p55Gag polyprotein precursor, and it was proposed that Env internalization is a means to evade immune recognition and proceeds until sufficient Gag has assembled at the PM to trap Env into the budding virion [67, 68].…”
Section: Introductionmentioning
confidence: 99%
“…Several variations on this model have been proposed. In principle, one or more cellular proteins could serve as adapters to bridge the various viral components together (12,(22)(23)(24), although no specific cellular proteins have been definitively identified to fill this role. Alternatively, interactions with lipid microdomains, such as lipid rafts, could serve as the common element that interacts with both viral components.…”
mentioning
confidence: 99%